Indahnya Wisata Negeri di Atas Awan: Pemberdayaan Masyarakat untuk Mewujudkan Wisata Sehat di dusun Kediwung - Septian Emma Dwi Jatmika; Annisa Anna (IKIP PGRI Bojonegoro, 2021)
One of the tourist destinations in Kediwung hamlet is Panguk Hill. The beauty of the Panguk hills is amazing and very good, both for sunrise and sunset tours. Panguk hill is known as